'Gaelic a Recommendation': Language and Employment in the Nineteenth-Century Highlands. Issue 2 (November 2020) - Kidd, Sheila M.
Abstract : This article examines the linguistic landscape of the nineteenth-century Highlands through the lens of the labour market. It analyses a corpus of over 600 job advertisements seeking Gaelic speakers which appeared in the Inverness Courier between 1817 and 1899 and draws on a further 200 from selected years of the Glasgow Herald and The Scotsman . It examines the range of roles in which an ability to speak Gaelic, alongside English, was seen as either a necessity or advantageous by employers, considering in turn, education, health and social welfare, commerce, domestic service, law and order, estate and land, and the church. Some of the factors behind growing opportunities for skilled and semi-skilled Gaelic speakers are explored, such as the expansion of the health and welfare system in the wake of the 1845 Poor Law (Scotland) Act, and the accommodations made for the needs of Gaelic speakers when new roles were created. The continuing utility of Gaelic in Highland commerce also emerges as a counter to contemporary views of the language as unsuited for such transactional contexts. The evidence from these advertisements underlines the complexity of language usage in the Highlands in the nineteenth century as well as the need for further research to extend our understanding of the use of Gaelic in both public and private spheres.